Chihuahua: Un acceso de modernidad. Algo de su vida económica entre 1880 y 1920 - Leon Garcia, Ricardo (Universidad Autónoma de Nuevo León, 2021)
https://libros.uanl.mx/index.php/u/catalog/view/100/131/356